“Reading” ability of students in Nepal - Shrestha, Kumar Narayan (Journal of NELTA, 2018)
Reading is the main means of exposure for English as a second or foreign language learner. The present study aimed at finding out the reading comprehension ability (RCA) of the master level students, majoring in English at Tribhuvan University (TU), Nepal in relation to IELTS academic reading test. Administering a sample testand analyzing its data, it was found that the RCA of the master level students is not adequate in terms of IELTS standard since their RCA is 41% and the IELTS score is 3.70 band. This shows that they are at ‘Extremely Limited User’ level for the admission policies in IELTS recognised countries and not eligible to get the admission in the IELTS recognised Universities. The implication of the study is that there is a need for reading skills development programme incorporating the enhancement of inferential, predictive and interpretive skills. Journal of NELTA, Vol 20 No. 1-2, December 2015, Page: 41-50